CVD diamond detectors for fast VUV and SX-ray diagnostics on FTU. (23rd September 2021) - Bombarda, F.; Angelone, M.; Apruzzese, G.; Centioli, C.; Cesaroni, S.; Gabellieri, L.; Grosso, A.; Marinelli, M.; Milani, E.; Palomba, S.; Piergotti, V.; Pucella, G.; et al.
Abstract: The diagnostic performances of photodetectors based on Chemical Vapor Deposition (CVD) single crystal diamonds that were installed on one of the equatorial ports of the FTU tokamak during the last six months of operation of the machine are reported. Examples of plasma fast events have been collected in several different plasma conditions, confirming the fast response capabilities of diamond detectors and the high S/N ratio. During the runaway control and mitigation experiments, for example, the so-called Anomalous DopplerInstabilities were observed as sharp peaks of Ly- α emission caused by fast electrons hitting the wall, as a result of RE beam instabilities, perfectly correlated in time with other magnetic diagnostics and fast EC polychromator signals. Fast oscillations in the plasma emission are also observed in the presence of tearing modes, while other interesting observations relate to pellet ablation processes. The CVD diamond detectors were installed on FTU in view of their possible use for replacement of the Si photodiodes currently adopted for Soft X-ray tomography on future devices with harsher radiation environments. In fact, it was realized that the relatively flat response of the UV diamond sensor opened the possibility of using these detectors as bolometers. The first encouraging results have prompted launching an R&D program for the development of full-fledged diamond bolometers, which will be especially well suited for the coverage of the divertor and edge regions in high performance devices, in the energy range from 10 eV to about 20 keV.